2018
DOI: 10.4162/nrp.2018.12.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of perilla oil and alpha linolenic acid on SH-SY5Y neuronal cell death induced by hydrogen peroxide

Abstract: BACKGROUND/OBJECTIVEOxidative stress plays a key role in neuronal cell damage, which is associated with neurodegenerative disease. The aim of present study was to investigate the neuroprotective effects of perilla oil (PO) and its active component, alpha-linolenic acid (ALA), against hydrogen peroxide (H2O2)-induced oxidative stress in SH-SY5Y neuronal cells.MATERIALS/METHODSThe SH-SY5Y human neuroblastoma cells exposed to 250 µM H2O2 for 24 h were treated with different concentrations of PO (25, 125, 250 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…Similar to previous reports, the fatty acid composition analysis of PO used in our study showed that a-linolenic acid was in the highest amount (59.5%, omega-3 fatty acid), followed by oleic acid (14.2%, monounsaturated fatty acid), linoleic acid (12.3%, omega-6 fatty acid), and palmitic acid (5.8%, saturated fatty acid). 28,29 The main fatty acids present in FO used in this study were EPA (15%, omega-3 fatty acid), DHA (15%, omega-3 fatty acid), palmitic acid (20%, saturated fatty acid), palmitoleic acid (14%, monounsaturated fatty acid), oleic acid (12%, monounsaturated fatty acid), linoleic acid (<3%, omega-6 fatty acid), and linolenic acid (<3%, omega-3 fatty acid).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous reports, the fatty acid composition analysis of PO used in our study showed that a-linolenic acid was in the highest amount (59.5%, omega-3 fatty acid), followed by oleic acid (14.2%, monounsaturated fatty acid), linoleic acid (12.3%, omega-6 fatty acid), and palmitic acid (5.8%, saturated fatty acid). 28,29 The main fatty acids present in FO used in this study were EPA (15%, omega-3 fatty acid), DHA (15%, omega-3 fatty acid), palmitic acid (20%, saturated fatty acid), palmitoleic acid (14%, monounsaturated fatty acid), oleic acid (12%, monounsaturated fatty acid), linoleic acid (<3%, omega-6 fatty acid), and linolenic acid (<3%, omega-3 fatty acid).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the positive impact of LNA's metabolites, such as eicosapentaenoic acid (EPA) and DHA, on learning-related memory in young and old rats [10,24] as well as Alzheimer's disease (AD) in model rats [25,26], linoleic acid (LLA), being the precursor of EPA and DHA, is also gaining increasing interest for improving brain cognition. Direct application of purified LNA to glial cell lines inhibited Amyloid β-induced oxidative stress [27]. Neuronal cell lines pretreated with LNA also inhibited H 2 O 2 -induced apoptotic neuronal cell death [28], thus suggesting that LNA has significant antioxidative potential.…”
Section: Introductionmentioning
confidence: 95%
“…It was reported that H 2 O 2 activated nuclear translocation of nuclear factor-kappa B (NF-κB) in SH-SY5Y cells and it up-regulated COX-2 and inducible nitric oxide synthase (iNOS) in the inflammatory pathway [26]. Our previous study also demonstrated that H 2 O 2 activated apoptosis pathway in SH-SY5Y cells and several therapeutic agents reduced the cell death [5].…”
Section: Discussionmentioning
confidence: 91%
“…Oxidative stress is generated in living organisms when the homeostasis between the production of free radicals and antioxidant defense system gets out of balance [4]. Previous studies demonstrated that oxidative stress exerts cellular damage including DNA injury, inflammation, and apoptosis of brain cells including neuronal, glial, and cerebrovascular cells [5][6][7]. High concentrations of reactive oxygen species (ROS) can cause damage to cellular lipids, proteins, and DNA because of strong reactivity [8].…”
Section: Introductionmentioning
confidence: 99%